RESORT PANTAI BATAKAN BARU - Farah Azkia Andini; Naimatul Aufa (ULM Press, 2023)
Geographically, Indonesia is an agricultural country with a very wide area and many have abundant natural resources, one of which is the beach which is often used by the government as a tourism industry sector. When viewed from the flow of tourist visitor growth in South Kalimantan, it has surged every year. In order for the development of the tourism sector of Batakan Baru Beach to increase, facilities and accommodations are needed that can accommodate all tourist activities. The right choice of accommodation facilities is a resort with a coast to coast glamping resort concept with a biomorphic architecture analogy design method. The choice of this concept is able to solve design problems that are disaster responsive and environmentally friendly and able to shape the behavior of visitors to participate in protecting the environment.